Implementasi Permainan Mini Maze Mengemudi Untuk Peningkatan Kognitif Anak Usia 4-5 Tahun - Risani, Kholifah Hayyu; Muthohar, Sofa (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2024)
The purpose of this study was to implement a mini maze driving game to improve the cognitive abilities of children aged 4-5 years. One aspect of child development that must be met is the cognitive aspect. In addition, teachers must also be creative in creating an interesting learning atmosphere so that all aspects of child development can be met. This study used a descriptive qualitative method. The location of the study was at KB-RA Al-Azhar Mosque in Group A aged 4-5 years. The data collection techniques used were observation, interviews and documentation. Data analysis used interactive analysis. The results of the study proved that the implementation of this mini maze driving game can improve children's cognitive abilities which include first, problem-solving skills in the form of the ability to find solutions when choosing the wrong path. Second, developing logical thinking skills where children are trained to think to find the right path. Third, symbolic thinking skills such as knowing geometric shapes, namely circles, squares, and rectangles.